Risk Factors for Anxiety in Major Depressive Disorder Patients - Xin, Li-Min (Clin Psychopharmacol Neurosci, 2015)
OBJECTIVE: To analyze the sociodemographic and clinical factors related to anxiety in patients with major depressive disorder (MDD). METHODS: This study involved a secondary analysis of data obtained from the Diagnostic Assessment Service for People with Bipolar Disorders in China (DASP), which was initiated by the Chinese Society of Psychiatry (CSP) and conducted from September 1, 2010 to February 28, 2011. Based on the presence or absence of anxiety-related characteristics, 1,178 MDD patients were classified as suffering from anxious depression (n=915) or non-anxious depression (n=263), respectively. RESULTS: Compared with the non-anxious group, the anxious-depression group had an older age at onset (t=−4.39, p<0.001), were older (t=−4.69, p<0.001), reported more lifetime depressive episodes (z=−3.24, p=0.001), were more likely to experience seasonal depressive episodes (χ(2)=6.896, p=0.009) and depressive episodes following stressful life events (χ(2)=59.350, p<0.001), and were more likely to have a family history of psychiatric disorders (χ(2)=6.091, p=0.014). Their positive and total scores on the Mood Disorder Questionnaire (MDQ) and the 32-item Hypomania Checklist (HCL-32) (p<0.05) were also lower. The logistic regression analysis indicated that age (odds ratio [OR]=1.03, p<0.001), a lower total MDQ score (OR=0.94, p=0.011), depressive episodes following stressful life events (OR=3.04, p<0.001), and seasonal depressive episodes (OR=1.75, p=0.039) were significantly associated with anxious depression. CONCLUSION: These findings indicate that older age, fewer subclinical bipolar features, an increased number of depressive episodes following stressful life events, and seasonal depressive episodes may be risk factors for anxiety-related characteristics in patients with MDD.